Transmission of dengue virus with and without vaccination using SIR Model / Norlaila Md Nor ...[et al.] - Md Nor, Norlaila; Mahmud, Maziah; W Ramli, Wan Khairiyah Hulaini; Jauhari, Nur Elini; Muzaffar, Nursyahirah Izzatie; Azman, Najwa Arni; Abdul Fatah, Siti Nur Umairah (Unit Penerbitan UiTM Kelantan, 2021)
Dengue is a mosquito-borne aggressive disease. The Susceptible-Infected-Recovered (SIR) model for the transmission of dengue virus is discussed. This project focused the dengue transmission into three compartments, namely, susceptible, infected and recovered for dengue transmission. The focus was to deduce the SIR model to find the base reproductive number Ro analytically. The SIR model was used to investigate the stability analysis of disease free and endemic for dengue transmission with and without vaccination by solving the Ordinary Differential Equation (ODE). In addition, SIR model was also used to analyze and predict the spread of dengue virus with and without vaccination. The transmission of dengue was studied using data taken from Thailand by observing the graph of population of dengue versus time in years for all three compartments of the SIR model. The graph will be plotted using MAPLE software. As a result of the stability analysis, it shows that the transmission of the dengue virus without vaccination will make the system unstable because not all of the roots are negative and the transmission of dengue with vaccination for both disease free and endemic will make the system stable.